Microleakage of Dyract AP compomers in class V preprations of deciduous teeth after air-dried versus not dried salivary contamination at the occlusal wall (in vitro study) (Mustansiria Dental Journal, 2018)
This in vitro study was conducted to asses the affect of salivary contamination incase of air dried or not dried (kept moist) before the application of the bonding agent(prime and bond NT) on the microleakage of Dyract AP compomers (advanceperformance) in primary molars at the occlusal wall of class V preparations andcompare it to the standardized technique of application.Sixty class V cavities were prepared in 30 teeth (exfoliated primary molars), thecavities were prepared in the middle third of the buccal and lingual surface of eachcrown and randomly divided into three groups (each group consists of 20 cavities)Group (I): air-dried after salivary contamination, Group (II): not dried after salivarycontamination (kept moist), Group (III): with out salivary contamination. After theteeth were filled, stored in distilled water for 24 hours, thermocycled, stained withbasic fuchsin dye, sectioned to record the extend of dye penetration understereomicroscope. Results revealed that there is no difference in the linearmicroleakage among groups at the occlusl wall. Although the differences were notstatistically significant, greater microleakage was found in group (I) indicating that ifsalivary contamination occur, it is better to leave the preparation moist rather thancomplete air dryness.